Yoso Farm as a Model of Qur'anic Ecotheology: Reflections on Surah Al-An‘ām [6]: 99 in the Conservation of Nature and Plants - Lintang Dewi Fi'liya Putri (Ma'had Aly As'adiyah Sengkang, 2026)
QS. Al-An‘ām [6]: 99 affirms the ontological relationship between water, plants, and the continuity of life as an expression of Divine power and an ecological mandate for humanity. This study examines the implementation of Qur’anic ecotheological values in sustainable agricultural practices at Yoso Farm, an agroecology community in Klaten, Central Java. Using a qualitative descriptive-analytical approach, the research combines a literature review of classical and contemporary tafsīr with field observations of Yoso Farm’s agricultural system. The analysis focuses on how religious values are integrated into agroecology-based environmental management. The findings indicate that Yoso Farm embodies the principles of mīzān (balance) and maṣlaḥah (public good) as implied in QS. Al-An‘ām [6]: 99. These practices frame environmental stewardship as ‘ibādah and affirm the human role as khalīfah, offering a Qur’an-based framework for sustainable development rooted in Islamic spirituality.